Patterns and predictors of first-line taxane use in patients with metastatic triple-negative breast cancer in US clinical practice - O’Shaughnessy, Joyce; Emens, Leisha A.; Chui, Stephen Y.; Wang, Wei; Russell, Kenneth; Lin, Shih-Wen; Flores Avile, Carlos; Luhn, Patricia; Schneeweiss, Andreas (Current oncology, 2021)
We investigated first-line (1L) treatment patterns and predictors of taxane use to better understand the evolving metastatic triple-negative breast cancer (mTNBC) treatment landscape. This retrospective analysis of the Truven Health MarketScan® (Somers, NY, USA) Database included women with mTNBC who received 1L therapy within six months of diagnosis (January 2005-June 2015). Multivariate logistic regression models identified predictors of taxane use, adjusting for prognostic factors. A total of 2271 women with newly diagnosed mTNBC received 1L treatment during the study period. Half received a 1L taxane (53%), more often in combination than as monotherapy (58% versus 42%), though this varied by specific taxane. Nab-Paclitaxel monotherapy increased substantially after 2010. More recent treatment year (odds ratio, 2.16 (95% CI 1.69-2.76]) and number of metastases (≥3 versus 1: 1.73 (1.25-2.40)) predicted taxane monotherapy versus combination. Having a health maintenance organization versus a preferred provider organization plan predicted less nab-paclitaxel versus paclitaxel (0.32 (0.13-0.80)) or docetaxel (0.30 (0.10-0.89)) use. More recent index year (2011-2015 vs. 2005-2010) was the only predictor favoring nab-paclitaxel versus paclitaxel (2.01 (1.26-3.21)) or docetaxel (3.63 (2.11-6.26)). Taxane-containing regimens remained the most common 1L mTNBC treatments. Paclitaxel and nab-paclitaxel use changed substantially over time, with nab-paclitaxel use associated with insurance coverage.
Gesehen am 20.01.2022